The effect of prior heavy exercise on the parameters of the power-duration curve for cycle ergometry - Miura, A.; Shiragiku, C.; Hirotoshi, Y.; Kitano, A.; Endo, M. Y.; Barstow, T. J.; Morton, R. H.; Fukuba, Y. (Applied Physiology, Nutrition, and Metabolism, 2009)
The tolerable duration (t) of high-intensity cycle ergometry is well characterized by a hyperbolic function of power output (P) with an asymptote (termed the critical power (CP)) and a curvature constant (denoted W'). The purpose of this study was to investigate the effect of prior heavy exercise (W-up) that specifically engenders an acidosis on CP and W'. Eight healthy subjects performed 2 sets of 4 high-intensity square-wave exercise bouts on a bicycle ergometer to estimate CP and W', with (W-up) and without (control) prior exercise, respectively. Exercise intensities of the 4 main bouts were selected in the range of 90% to 135% peak oxygen uptake so as to reach the limit of tolerance between approximately 1.5 and 10 min. The W-up bout was preceded by 6 min cycling at a work rate halfway between the lactate threshold and peak oxygen uptake (mean ± SD of 153.8 ± 29.8 W) starting 12 min before the main bout. Blood lactate levels ([La]b) just before the main exercise bouts in W-up conditions were significantly higher than those of the control (4.7 ± 1.1 and 1.4 ± 0.4 mEq·L-1, respectively; p < 0.05). However, there were no significant differences in end-exercise [La]b. W-up increased significantly the tolerable duration at every work rate compared with the control, which was attributable exclusively to increased CP (176.5 ± 34.3 and 168.7 ± 31.3 W, respectively; p < 0.05), without any significant change in W' (11.0 ± 3.2 and 11.0 ± 3.1 kJ, respectively). It is concluded that the prior heavy exercise improved performance mainly because of an enhanced aerobic component of exercise energetics, as indicated by a higher CP and lower increment in the [La]b.